Comparative Evaluation of Microbiota Engraftment Following Fecal Microbiota Transfer in Mice Models: Age, Kinetic and Microbial Status Matter - Le Roy, Tiphaine; Debédat, Jean; Marquet, Florian; Da-Cunha, Carla; Ichou, Farid; Guerre-Millo, Michèle; Kapel, Nathalie; Aron-Wisnewsky, Judith; Clément, Karine (Frontiers in Microbiology, 2019)
The intestinal microbiota and its functions are intricately interwoven with host physiology. Colonizing rodents with donor microbiota provides insights into host-microbiota interactions characterization and the understanding of disease physiopathology. However, a better assessment of inoculation methods and recipient mouse models is needed. Here, we compare the engraftment at short and long term of genetically obese mice microbiota in germ-free (GF) mice and juvenile and adult specific pathogen free (SPF) mice. We also tested the effects of initial microbiota depletion before microbiota transfer. In the present work, donor microbiota engraftment was better in juvenile SPF mice than in adult SPF mice. In juvenile mice, initial microbiota depletion using laxatives or antibiotics improved donor microbiota engraftment 9 weeks but not 3 weeks after after microbiota transfer. Microbiota-depleted juvenile mice performed better than GF mice 3 weeks after the microbiota tranfer. However, 9 weeks after transfer, colonized GF mice microbiota had the lowest Unifrac distance to the donor microbiota. Colonized germ-free mice were also characterized by a chronic alteration in intestinal absorptive function. With these collective results, we show that the use of juvenile mice subjected to initial microbiota depletion constitutes a valid alternative to GF mice in microbiota transfer studies.